Osteodiscus abyssicola, a new snailfish (Cottoidei: Liparidae) collected off the Pacific coast of northern Japan - Murasaki, Kenta; Kai, Yoshiaki; Endo, Hiromitsu; Fukui, Atsushi (Zootaxa, 2021)
The snailfish Osteodiscus abyssicola sp. nov. is described from a single specimen collected off the Pacific coast of Hokkaido, northern Japan, at a depth of 4,671–4,744 m. It is distinguished from all currently recognized congeners by the following combination of characters: vertebrae 49; dorsal-fin rays 44; anal-fin rays 39; principal caudal-fin rays 8; pyloric caeca 5; mouth horizontal; teeth on both jaws simple and sharp, without cusps; upper and lower jaw symphyses without diastema; cephalic pore sizes moderate, similar to or slightly larger than nostril; gill slit extending ventrally to 2nd pectoral-fin ray base; pectoral fin notched; mandibular symphysis to center of anus 101.6% head length (HL); posterior edge of pelvic disk to center of anus 15.5% HL; epural 1, reduced; epipleural ribs absent. An emended diagnosis and key to the species of Osteodiscus are provided.